Prevalence of molluscum contagiosum disease in day care centers in Babol, Northern Iran - Tabari, Soudabeh Tirgar; Shakerian, Mohammad Ali (Journal of Pediatric Infectious Diseases, 2007)
Molluscum contagiosum is a viral skin disease commonly affects children. The purpose of this study was to determine the prevalence of molluscum contagiosum in day care centers in Babol, Northern Iran. This cross-sectional study was performed on 986 children from 19-day care centers; in the second half of 2005. Obtained data in all children were analyzed. Four hundred sixty seven girls and 519 boys aged between 1.5–5 years were evaluated. The prevalence of molluscum contagiosum in girls was 1.7% and in the boys was 2.5% (P > 0.05). Overall prevalence of molluscum contagiosum in day care centers was 2.12%. The prevalence of disease in children aged between 2–4 years was higher than those other children (3.6%) (P = 0.038). The results show that the prevalence of molluscum contagiosum in day care centers is relatively low, but the prevalence in the age of 2–4 years was the highest. In view of contagious nature of the disease, it is recommended that medical examination of children should include a proper examination of the entire skin before admission into day care centers.
Keywords: Prevalence; molluscum contagiosum; day care center